Evaluation of the effectiveness of three physiotherapeutic treatments for subacromial impingement syndrome: a randomised clinical trial. Issue 1 (March 2016) - Pérez-Merino, L.; Casajuana, M.C.; Bernal, G.; Faba, J.; Astilleros, A.E.; González, R.; Giralt, M.; Romeu, M.; Nogués, M.R.
Abstract: Objective: To determine whether dexketoprofen administered by phonophoresis or iontophoresis is more effective for the treatment of subacromial impingement syndrome (SIS) than conventional ultrasound therapy. Design: Randomised clinical trial. Setting: University hospital. Participants: Ninety-nine participants with SIS without a complete tear of the rotator cuff were assigned at random to three intervention groups. Intervention groups: Participants received ultrasound ( n = 32), phonophoresis with dexketoprofen (50 mg/session) ( n = 33) or iontophoresis with dexketoprofen (50 mg/session) ( n = 34). All participants completed 20 treatment sessions plus exercise therapy and cryotherapy. Outcome measures: A visual analogue scale (VAS), the Constant–Murley Scale (CMS) and the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire were administered pre-treatment (baseline), post-treatment and 1 month post-treatment. Results: At baseline, there were no differences between the groups. Post-treatment, VAS score improved by −1.2 points and CMS score improved by 8.9 points in the ultrasound group compared with the iontophoresis group [95% confidence interval (CI) −0.2 to −2.2 and 95% CI 17.0 to 0.7, respectively]. CMS score improved by 7.1 points in the phonophoresis group compared with the iontophoresis group (95% CI 14.8 to −0.7). At 1 month post-treatment, no significant differences were detected between the groups. VAS, CMS and DASH scores of all groups improved post-treatment and at 1 month post-treatment. Conclusion: Ultrasound, iontophoresis with dexketoprofen and phonophoresis with dexketoprofen can improve pain, shoulder function, and physical functioning and symptoms in the upper limb in patients with SIS without a complete tear of the rotator cuff. Clinical Trials.gov registration number: NCT01748188 .